2017
DOI: 10.1371/journal.pone.0186060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pharmaceutical marketing on Medicare prescriptions in the District of Columbia

Abstract: ImportanceGifts from pharmaceutical companies are believed to influence prescribing behavior, but few studies have addressed the association between industry gifts to physicians and drug costs, prescription volume, or preference for generic drugs. Even less research addresses the effect of gifts on the prescribing behavior of nurse practitioners (NPs), physician assistants (PAs), and podiatrists.ObjectiveTo analyze the association between gifts provided by pharmaceutical companies to individual prescribers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 28 publications
(25 reference statements)
0
34
0
Order By: Relevance
“…It is clear that substantial sums are spent on marketing: $17 700m on medical marketing in 1997, which rose to $20 900m in 2016 . Marketing is not always constrained by ethics or self‐regulation: between 2003 and 2012, there were 74 cases of off‐label promotion in the United Kingdom, and 43 companies were ruled in breach of the relevant regulation at least once . It is also clear that prescribers are influenced by such marketing.…”
Section: Problemsmentioning
confidence: 99%
“…It is clear that substantial sums are spent on marketing: $17 700m on medical marketing in 1997, which rose to $20 900m in 2016 . Marketing is not always constrained by ethics or self‐regulation: between 2003 and 2012, there were 74 cases of off‐label promotion in the United Kingdom, and 43 companies were ruled in breach of the relevant regulation at least once . It is also clear that prescribers are influenced by such marketing.…”
Section: Problemsmentioning
confidence: 99%
“…To the best of our knowledge no previous study has analysed the financial relationships of clinical practice guideline committee members of infectious diseases, and this study revealed for the first time that manufacturers of anti-MRSA drugs made large payments to Japanese MRSA clinical practice guidelines authors, totalling nearly V240 000. Such financial ties should raise concerns, considering the current perception of appropriate relationships between physicians and the industrial companies, because several researchers have reported that financial conflicts of interest contribute to promotion of specific drugs, and affect the physicians' prescription decisions [2,17]. Unlike the other 40 companies, these five anti-MRSA drug companies paid particularly for speaking.…”
Section: Industrial Involvement In Developing Clinical Practice Guidementioning
confidence: 99%
“…Interactions with the pharmaceutical and device manufacturers in particular may give rise to cognitive biases regarding use of relevant pharmaceuticals and devices. [63, 64] Physicians should actively avoid, and be protected from, exposure to direct and indirect marketing efforts of drug and device manufacturers.…”
Section: The Role Of Cognitive Biasesmentioning
confidence: 99%